The Organ Size and Morphological Change During the Domestication Process of Soybean - Zhou, Xuan; Wang, Dongfa; Mao, Yawen; Zhou, Yueqiong; Zhao, Limei; Zhang, Chunbao; Liu, Yu; Chen, Jianghua (Frontiers in Plant Science, 2022)
Soybean is one of the most important legume crops that can provide the rich source of protein and oil for human beings and livestock. In the twenty-one century, the total production of soybean is seriously behind the needs of a growing world population. Cultivated soybean (Glycine max [L.] Merr.) was domesticated from wild soybean (G. soja Sieb. & Zucc.) with the significant morphology and organ size changes in China around 5000 years ago, including twisted stems to erect stems, small seeds to large seeds. Then it was spread worldwide to become one of the most popular and important crops. The release of the reference soybean genome and omics data provides powerful tools for researchers and breeders to dissect the functional genes and apply the germplasm in their work. Here, we summarized the function genes related to yield traits and organ size in soybean, including stem growth habit, leaf size and shape, seed size and weight. In addition, we also summarized the selection of organ traits during soybean domestication. In the end, we also discussed the application of new technology including the gene edit on the basic research and breeding of soybean, and the challenges and research hotspots in the future.